Ovarian and Uterine Grafts: (Section of Obstetrics and Gynæcology) - Cheval, Max (1934)
Recent experience has convinced the author of the value of ovarian grafting. He gives the histories of a number of women upon whom he made implants of their own ovarian tissue in the course of operations for double oöphorectomy. The subsequent state of these patients is contrasted with that of women after castration without grafting. When the uterus was left in position menstruation was re-established in over 80% of the grafted cases. The author and his co-workers maintain that the vitality of autogenous grafts of ovarian substance is enhanced by hormones produced by the uterine mucosa. He therefore advocates that grafts of uterus be made in conjunction with ovarian implants whenever possible. Experiments carried out on animals have proved the correctness of this opinion. The results of a series of cases of combined ovarian and uterine graftings are recorded, and the technique of uterine mucosa implants is described.